The Potential Role of Heparin in Patients With COVID-19: Beyond the Anticoagulant Effect. A Review - Gozzo, Lucia; Viale, Pierluigi; Longo, Laura; Vitale, Daniela Cristina; Drago, Filippo (Frontiers in Pharmacology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is responsible of variable clinical manifestations, ranging from no symptoms to severe pneumonia with acute respiratory distress syndrome, septic shock, and multi-organ failure resulting in death. To date no specific antiviral drug have been approved for COVID-19, so the treatment of the disease is mainly focused on symptomatic treatment and supportive care. Moreover, there are no treatments of proven efficacy to reduce the progression of the disease from mild/moderate to severe/critical. An activation of the coagulation cascade leading to severe hypercoagulability has been detected in these patients, therefore early anticoagulation may reduce coagulopathy, microthrombus formation, and the risk of organ damages. The role of heparin in COVID-19 is supported by a lot of studies describing its pleiotropic activity but it must be proven in clinical trials. Several protocols have been designed to assess the risk-benefit profile of heparin (low-molecular-weight or unfractionated heparin) in hospitalized subjects. Although prophylactic doses may be adequate in most patients, it is important to wait the results of clinical trials in order to define the appropriate effective dose able to improve disease outcome.